Association of different cell types and inflammation in early acne vulgaris - Huang, Lei; Yang, Shuyun; Yu, Xiuqin; Fang, Fumin; Zhu, Liping; Wang, Lu; Zhang, Xiaoping; Yang, Changzhi; Qian, Qihong; Zhu, Tingting (Frontiers in Immunology, 2024)
Acne vulgaris, one of the most common skin diseases, is a chronic cutaneous inflammation of the upper pilosebaceous unit (PSU) with complex pathogenesis. Inflammation plays a central role in the pathogenesis of acne vulgaris. During the inflammatory process, the innate and adaptive immune systems are coordinately activated to induce immune responses. Understanding the infiltration and cytokine secretion of differential cells in acne lesions, especially in the early stages of inflammation, will provide an insight into the pathogenesis of acne. The purpose of this review is to synthesize the association of different cell types with inflammation in early acne vulgaris and provide a comprehensive understanding of skin inflammation and immune responses.